2012
DOI: 10.1021/bi201843b
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal Extension of Chloroplast 2-Cys Peroxiredoxin Is Critical for Interaction with ATP

Abstract: 2-Cys peroxiredoxins (2-Cys Prxs) are ubiquitous enzymes that have been implicated in peroxide-mediated signaling of markedly different processes, such as cancer and photosynthesis. A highly conserved C-terminal extension of eukaryotic homologues modulates both the overoxidation of cysteines and the formation of oligomers. Here, we reveal that the plant counterpart regulates the self-polymerization of 2-Cys Prx triggered by ATP and Mg(2+). This feature is of particular importance under oxidative stress because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The formation of the spherical HMW complex by plant Prx requires only Mg 2+ /ATP, and this process is not affected by its redox state. , In addition, the C-terminal region of plant Prx (residues 183–200) is important for the formation of these spherical complexes . In contrast, we previously showed that the Prx2 oligomer lacking phospholipids did not interact with Mg 2+ /ATP or Mg 2+ /ADP to form the HMW complex .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The formation of the spherical HMW complex by plant Prx requires only Mg 2+ /ATP, and this process is not affected by its redox state. , In addition, the C-terminal region of plant Prx (residues 183–200) is important for the formation of these spherical complexes . In contrast, we previously showed that the Prx2 oligomer lacking phospholipids did not interact with Mg 2+ /ATP or Mg 2+ /ADP to form the HMW complex .…”
Section: Resultsmentioning
confidence: 98%
“…22,23 In addition, the C-terminal region of plant Prx (residues 183− 200) is important for the formation of these spherical complexes. 24 In contrast, we previously showed that the Prx2 oligomer lacking phospholipids did not interact with Mg 2+ / ATP or Mg 2+ /ADP to form the HMW complex. 19 To investigate the role of the C-terminus in the formation of the Prx2 HMW complex, we prepared a C-terminal-truncated Prx2 (Prx2 Δ181−198 ).…”
Section: ■ Results and Discussionmentioning
confidence: 99%